Fortifikasi fraksi tidak tersabunkan (ftt) distilat asam lemak minyak sawit pada roti tawar: implikasi pada sifat fisik dan sensoris - Kgs Ahmadi; Teti Estiasih (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Palm Fatty Acid Distillate (PFAD) is by product from palm oil industry which contains free fatty acid and bioactive in minor component. Saponification of free fatty acid causes to formation soap and unsaponifiable matter (tocopherol, tocotrienol, phytosterol, and squalene. This research aims to determine the effect fortification unsaponifiable matter on physical and sensory properties of bread. The experiment design used Complete Randomized Design of one factor, namely level of unsaponifiable matter sequentially 0; 0.5; 1.0; 1.5; 2.0; and 2.5% in four times replication. Observation parameters of physical properties: developmental volume, texture, and bulk density. While sensory characteristics are color, aroma, taste, and texture. This research showed that fortification of unsaponifiable matter did not affect physical properties (development volume, texture, and bulk density). Sensory test results without unsaponifiable matter fortification are the best treatment for color, aroma, taste, and texture, while among those fortified with unsaponifiable matter the level of 0.5% is a level that is still acceptable to panelists.